“People are shortening the lifetime of mentally ill persons”; Community’s perception towards mental illness and help-seeking behavior in Bench Sheko, Sheka, Kaffa and West Omo zones, South West Ethiopia, 2021 - Nahom Solomon Habtamu; Gebremeskel Mesafint; Kidus Yenealem; Sewagegn Demelash; Zenebu Muche; Dawit Getachew (PLoS ONE, 2025)
Background Mental diseases or mental disorders are conditions that affect the mind and are defined by changes in emotion, thought, or behavior. Many studies have demonstrated that people with mental illnesses are not receiving the necessary care and treatments, despite the fact that they need basic healthcare services and supportive strategies. Particularly in Ethiopia, there is a severe paucity of research on the topic. The aim of this study was to investigate how South West Ethiopians perceive and act when seeking treatment for mental illness. Methods We conducted a descriptive qualitative study in Bench-Sheko, Kaffa, West Omo, and Sheka Zones, Southwest Ethiopia, from February to May 30, 2021. A purposively selected 58 individuals were interviewed by research experts using interview guides and responses were audio recorded. The recorded data were transcribed verbatim and analyzed by following a thematic analysis approach and the findings were narrated by supporting with quotes. Results In this study, 58 participants took part, and they were let to discuss on: the definitions of mental disease, its origins and symptoms, caregiving practices, methods of treatment, and difficult tasks related to mental illness. The study showed that people’s perceptions and descriptions of people with mental illnesses, as well as how they interact with and behave when seeking care, were discriminatory. In the early stages of the illness, some family members attempt to take the mentally ill individuals to their respective places of worship, but very rarely to medical facilities. However, as the illness progresses, almost all mentally ill individuals are typically left to live on the streets, where they frequently encounter prejudice and social exclusion. Conclusion The local community does not take a supportive stance toward those who are mentally ill, and there is no formalized system in place for them to receive care and treatment. Few people who are willing to give them food, clothing, and shelter were proven to have the power to influence their fate. Therefore, it is crucial to provide mental health services to those in need and develop effective awareness-raising initiatives, especially by working with local authorities, religious leaders, and other influential individuals.